The Effect of Service Quality, Brand Image, and Customer Satisfaction on Customer Loyalty in Go Food Services - Azeem Athallah Malik; Muchsin Muthohar (Jurnal Economic Resource, 2023)
Customer loyalty is a major factor for success in doing business, customer loyalty in doing business is influenced by service quality, brand image, and consumer satisfaction. This study aims to identify the effect of service quality, brand image, and customer satisfaction on customer loyalty at Go Food. This study used a non-probability convenience sampling technique in sampling. Primary data collected in this study amounted to 250 respondents. The statistical analysis technique used in this study is Structural Equation Modelling (SEM) with Smart PLS version 3.2.9 software. The results of the data analysis show that service quality has a positive and significant influence on brand image, customer satisfaction, and customer loyalty. Brand image has a positive and significant influence on customer satisfaction and loyalty, as well as customer satisfaction which has a positive and significant influence on customer loyalty.